Biodegradation of Polyethylene Microplastic using Culturable Coral-Associated Bacteria Isolated from Corals of Karimunjawa National Park - Prastyo Abi Widyananto; Sakti Imam Muchlissin; Agus Sabdono; Bambang Yulianto; Fauziah Shahul Hamid; Ocky Karna Radjasa (Ilmu Kelautan)
Polyethylene is a plastic material that was globally produced and is well known as a non-degradable pollutant product. Plastic pollution, primarily microplastics, have been distributed to coral reef ecosystems, where these areas are ecosystems with high productivity. Karimunjawa National Park in Indonesia is one of the protected areas for coral reef ecosystem habitat in Central Java, threatened by microplastic contamination. Recent studies have shown that coral-associated bacteria have an adequate ability to degrade marine pollutant materials. No one has reported that the use of indigenous coral-associated bacteria has the potential for microplastic biodegradation, especially low-density polyethylene microplastic materials. Hence, the objective of this study was to find the potential of microplastic biodegradation agents derived from coral-associated bacteria in Karimunjawa National Park area. Various coral life-forms were isolated in July 2020 from conservation areas and areas with anthropogenic influences. Bacterial isolates were screened using tributyrin and polycaprolactone as substrates to reveal potential microplastic degradation enzymes. The total isolation results obtained 92 bacterial isolates, and then from the result of enzyme screening, there were 7 active bacteria and only 1 bacteria that potential to degrade polyethylene. LBC 1 showed that strain could degrade by 2.25±0.0684 % low-density polyethylene microplastic pellet by incubating bacterial growth until the stationary phase. Identification of LBC 1 strain was carried out by extracting DNA and bacterial 16S rRNA sequences. Bacterial gene identification refers to Bacillus paramycoides with a similarity level in the National Center Biotechnology Information database of 99.44%. These results prove that hard coral association bacteria can degrade low-density polyethylene microplastics.